Xuesanqi ameliorates DSS-induced colitis in mice by mediating gut microbiota dysbiosis and modulating MAPK/ERK/JNK pathway - Qiyuan Su; Qian Hu; Songtao Wu; Suqin Yang; Hanwen Su; Zhengjun Zhang; Chengxiu Ling (Natural Products and Bioprospecting)
Abstract This study aimed to evaluate the therapeutic properties of the traditional Chinese medicine Xuesanqi (XSQ, from the rhizome of Polygonum amplexicaule D. Don) in treating ulcerative colitis. We hypothesized that its many active components can alleviate symptoms of colitis by regulating the gut microbiota, its metabolites, and various signaling pathways. To test our hypotheses, we designed a DSS- induced colitis model in C57BL/6 male mice. Apparent metrics were evaluated in each group of mice and performed histological analysis of relevant tissues. The gut microbial composition was analyzed by 16S rRNA sequencing of bacteria. Simultaneously, the SCFAs content was detected by gas chromatography, inflammatory factor secretion was evaluated by ELISA or western-blot, the expression of tight junction protein and key proteins of the MAPK signaling pathway were analyzed by western-blot. Our result showed that the treatment with XSQ alleviated significant various symptoms such as weight loss, blood in stool, and shortening of colon. In addition, XSQ treatment restored the dysregulated gut microbiota in colitis mice, increased short chain fatty acids (SCFAs) and normalized the MAPK/ERK/JNK signaling pathways, promoted expression of tight junction protein Occludin, Claudin-1, and E-cadherin proteins. Furthermore, we also observed a dose-dependent pattern in these treatment responses. These findings demonstrated the active components of XSQ is a promising new treatment platform for ulcerative colitis. Graphical Abstract